Savings services for the poor : an operational guide - Hirschland, Madeline (Bloomfield, CT : Kumarian Press, 2005)
"Contains practical guidance for managing sounds savings operations for small and rural depositors. The book addresses two types of institutions: microfinance institutions and mainstream banks"--Provided by publisher.
Includes bibliographical references and index.
opc 27/09/16, ijb 21/02/2019
Loans
Keywords: Poor; Savings accounts; Saving and investment; Savings banks; Banks and banking; Bank management